How artificial intelligence can improve digital marketing - Pereira, L. (2023)
Recent technological advances have allowed the growth of digital marketing, creating the challenge of big data. AI emerges to deal with this paradigm and marketing becomes a natural beneficiary, as it takes advantage of data in its processes. This research aims to evaluate the potential impact of AI on digital marketing. This knowledge could accelerate the adoption of AI technologies, revolutionising the area. The following techniques were developed: survey for digital marketing professionals to identify their needs; research of AI solutions; coverage and match analysis between needs and solutions. This research establishes which digital marketing aspects need further development and recommends response solutions: Bloomreach Experience Cloud for customer experience; Alli AI and Market Brew for SEO; concured for content marketing; Automizy for e-mail marketing; Cortex for social media marketing; Adobe Advertising Cloud for online advertising; Conversica and drift automation for communication; and SAS VDMML and SAS VF for data analysis.